Pengukuran level pembentukan es (ICING) pada pemodelan menggunakan rancang bangun sensor berbasis perubahan frekuensi dengan induktor datar - Yoga Dwi Cahyono; Samsul Hidayat; Nugroho Adi Pramono (Universitas Negeri Malang, 2021)
Icing is one of the main dangers for the flight and are cumulative. The icing is a process of accumulation of ice on parts of the aircraft, which will lead to changes in geometry and resulted in a variety of other disorders. For example, there was a buildup of ice on the propellor (propeller) and the engine carburetor so it can reduce the thrust plane even caused the plane to fall freely (stall). For it needs to be designed and built the Icing Detector as well as the actuator in providing early warning of the existence of the calculation and the icing on the pilot. This instrument is designed with electronic units that use the oscillator as frequency generator and frequency meter based mikrokontroller ATmega8 as the measuring frequency. The surface of the sensor is made up of printed inductor with a broad surface for detection area. Sensors and electronic units connected by cable. In addition, modeling for the pilot indicators have been designed using the LCD. Research results suggest that testing on